Proof: Subtract Substitute 2 Vars
Let's prove the following theorem:
if the following are true:
- a = b
- c = d
then a - c = b - d
Proof:
Given
1 | a = b |
---|---|
2 | c = d |
# | Claim | Reason |
---|---|---|
1 | a + (c ⋅ (-1)) = b + (c ⋅ (-1)) | if a = b, then a + (c ⋅ (-1)) = b + (c ⋅ (-1)) |
2 | c ⋅ (-1) = d ⋅ (-1) | if c = d, then c ⋅ (-1) = d ⋅ (-1) |
3 | a + (c ⋅ (-1)) = b + (d ⋅ (-1)) | if c ⋅ (-1) = d ⋅ (-1) and a + (c ⋅ (-1)) = b + (c ⋅ (-1)), then a + (c ⋅ (-1)) = b + (d ⋅ (-1)) |
4 | a + (c ⋅ (-1)) = a - c | a + (c ⋅ (-1)) = a - c |
5 | b + (d ⋅ (-1)) = b - d | b + (d ⋅ (-1)) = b - d |
6 | a - c = b - d | if b + (d ⋅ (-1)) = b - d and a + (c ⋅ (-1)) = a - c and a + (c ⋅ (-1)) = b + (d ⋅ (-1)), then a - c = b - d |
Comments
Please log in to add comments